Identification and distribution of fluoride in Singkep Island, Lingga Regency, Riau Islands - Razi, Faizal; Hendrayana, Heru; Harijoko , Agung (Brawijaya University, 2024)
The consumption of fluoride below the safe limit can result in dental caries, while high concentrations can lead to fluorosis, which can potentially impair the body's systems. One geological factor that influences the concentration of fluoride in water is the type of rock through which the water passes, including granite and its weathering products. The area is located within the Tandjungbuku Formation, which is predominantly composed of granite rock and contains several areas with Mining Business Permits (IUP) for commodities such as silica sand. This research serves as a form of mitigation in response to mining activities, post-mining, and the development of an industrial area. One anticipated impact is an increase in fluoride concentration in the research area, originating from both natural geological processes and human activities. The investigation involved geological mapping, petrographic analysis, XRD, and XRF analysis. Water sampling was conducted for both surface water and groundwater from wells in Resang Tandjungbuku Village. The research area consists of two rock units: granite, which acts as a non-aquifer layer, and colluvial deposits, which function as a free aquifer. Petrographic analysis identified minerals associated with fluoride, such as plagioclase, amphibole, and biotite. This was supported by XRD analysis with the presence of biotite, muscovite and kaoline minerals. XRF results revealed fluoride values in granite rock at 0.23% or 2300 ppm, further confirming granite as a source of fluoride. Analysis of fluoride in surface water showed values ranging from 0.01 to 4.24 mg/L, while groundwater consistently had a value of 0.01 mg/L.